ANALISIS PENYELENGGARAAN PELAYANAN PUBLIK: SURVEI INDEKS KEPUASAN MASYARAKAT DI PEMDA KABUPATEN JAYAPURA TAHUN 2019 - Alih Aji Nugroho; Keisha Dinya Sholihati; M. Rizki (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
Â Quality public service with a high level of community satisfaction are the determinants of the success of local governments in realizing good governance and sustainable development. This paper aims to present empirical data related to public service practices in Jayapura Regency. The purpose of this study is to precisely measure service quality; determine the satisfaction index; and perform a theoretical-conceptual study on the implementation of public service delivery in Jayapura Regency as mandated by Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia No.14 of 2017 on Guidelines of Public Satisfaction Surveys for Public Service. The research method used is descriptive quantitative. Primary data were collected from community satisfaction survey to obtain the Jayapura Regency Community Satisfaction Index (IKM). Based on results of data processing, CSI for Yowari Hospital of Jayapura District is 2,69, while CSI for DPMPTSP of Jayapura District is 2,91, and Dispendukcapil obtained an average CSI value of 2,83. The CSI value of those three RGOs are all categorized as â€œCâ€, defined as â€œNot Good Enoughâ€, which indicates that the need for public service management improvement is crucial, both in terms of infrastructure and employeeâ€™s competency in deliviring excellent services.